Review of Islamic Law Addressing Sexual Problems of Married and Wife Couples in LDR (Virtual Sex Law) - Yaqin, Ainul (Peneliti.net, 2025)
Sexual needs are included in the primary needs of a human being. While marriage is the provision of a container as a place to channel sexual desires in a halal and justified manner. The union of two people of the opposite sex in a marriage bond aims to create perfection in fulfilling the primary needs of both. However, in the relationship of LDR couples, they will encounter several problems related to the maximization of meeting the needs of both. So in this study we show how the Islamic review addresses the needs of LDR couples, especially in terms of their sexuality needs. Because they are separated by a long distance, the easiest thing for both couples to do is to utilize the sophistication of technology by having virtual intimacy. VCS (vido call sex), sexting, phond sex, using sex toys are some options for LDR couples to vent their biological desires. This phenomenon will be analyzed through a literature study by looking for the main references that mention similar discussions and then analyzed comprehensively based on scientific logic. Islamic teachings have rules related to these virtual sex fulfillment activities. Seeing the partner's aurat is permissible and worthy of reward for the couple either directly or through the media. While a further problem is the next action, namely the last effort to release sperm (orgasm) is something that is underlined. If it is done independently or with the help of tools, this is forbidden in Islamic teachings. Islam only allows the release of sperm through the right way, namely with the body of his wife (or slave).